A statistical analysis of the Ceres project - Bradshaw, Deborah (Department of Mathematics and Applied Mathematics, 2023)
This thesis has dual purpose of fulfilment of the requirements for the degree of Master of Science as well as a statistical report to Blair Research Laboratory, Salisbury, to whom I am indebted for allowing me to use the data they had collected. I am grateful to the director, Dr. V. de V. Clarke, for his help and co-operation. I thank all the members of the Department of Mathematical Statistics, University of Cape Town, for being most willing to help me, and in icu for the guidance given by my supervisor Professor C.G. Troskie as well as the help given by Associate Professor .H. Money. I a grateful to Dr. W. Hatchuel for arranging, and to Pfizer Laboratories (Pty) Ltd, for supplying I financial assistance which together with my bursary from the C. S. I. R. made it possible to complete this thesis. Lastly, but by no means least, I am indebted to Mrs. M.I. Cousins for so skilfully typing this thesis despite all the tables it contains.